Comparative Microbiological and Whole-Genome Analysis of Staphylococcus aureus Populations in the Oro-Nasal Cavities, Skin and Diabetic Foot Ulcers of Patients With Type 2 Diabetes Reveals a Possible Oro-Nasal Reservoir for Ulcer Infection - McManus, Brenda A.; Daly, Blánaid; Polyzois, Ioannis; Wilson, Pauline; Brennan, Gráinne I.; Fleming, Tanya E.; Grealy, Liam D.; Healy, Marie-Louise; Coleman, David C. (Frontiers in Microbiology, 2020)
Patients with type 2 diabetes are at higher risk for periodontal disease and diabetic foot ulcer infections (DFUIs), the latter of which are predominantly caused by staphylococcal bacteria. Staphylococci have also been detected in the mouth, nose and gums (the oro-nasal cavity) of patients with periodontal disease and can move between the mouth and nose. The present study investigated if the oro-nasal cavity and/or periodontal pockets in diseased gum tissue can provide a microbial reservoir for DFUIs. Eighteen patients with type 2 diabetes and at least three natural teeth (13 patients with ulcers and five patients without ulcers) underwent non-invasive microbiological sampling of periodontal pocket, oro-nasal, skin and ulcer sites. Staphylococci were recovered using selective chromogenic agar, definitively identified and subjected to DNA microarray profiling, whole-genome sequencing and core-genome multilocus sequence typing (cgMLST). Staphylococcus aureus and Staphylococcus epidermidis were recovered from both the oro-nasal and ulcer sites of 6/13 and 5/13 patients with ulcers, respectively. Molecular typing based on the staphylococcal protein A (spa) gene and DNA microarray profiling indicated that for each patient investigated, S. aureus strains from oro-nasal and ulcer sites were identical. Comparative cgMLST confirmed that isolates from multiple anatomical sites of each individual investigated grouped into closely-related, patient-distinct clusters (Clusters 1-7). Isolates belonging to the same cluster exhibited an average of 2.9 allelic differences (range 11). In contrast, reference genomes downloaded from GenBank selected as representatives of each sequence type identified in the present study exhibited an average of 227 allelic differences from the most closely related isolate within each cluster.